Evaluating the effectiveness of publishers’ features in fake news detection on social media - Jarrahi, Ali; Safari, Leila (Multimedia tools and applications, 2023)
With the expansion of the Internet and attractive social media infrastructures, people prefer to follow the news through these media. Despite the many advantages of these media in the news field, the lack of control and verification mechanism has led to the spread of fake news as one of the most critical threats to democracy, economy, journalism, health, and freedom of expression. So, designing and using efficient automated methods to detect fake news on social media has become a significant challenge. One of the most relevant entities in determining the authenticity of a news statement on social media is its publishers. This paper examines the publishers’ features in detecting fake news on social media, including Credibility , Influence , Sociality , Validity , and Lifetime . In this regard, we propose an algorithm, namely CreditRank, for evaluating publishers’ credibility on social networks. We also suggest a high accurate multi-modal framework, namely FR-Detect, for fake news detection using user-related and content-related features. Furthermore, a sentence-level convolutional neural network is provided to properly combine publishers’ features with latent textual content features. Experimental results show that the publishers’ features can improve the performance of content-based models by up to 16% and 31% in accuracy and F1, respectively. Also, the behavior of publishers in different news domains has been statistically studied and analyzed.